Imunomarcação e histomorfometria em procedimentos de regeneração tecidual guiada com membranas de látex, ptfe e de origem bovina - Ré, Gustavo Henrique Savariani de (2012)
Bone tissue regeneration capacity displays, but this is restricted in the presence of competitors tissues with high proliferative capacity. The objective of this study was to evaluate the immunostaining for markers of bone activity, and check the new formation of bone tissue in Guided Tissue Regeneration procedures with látex membrane, Polytetrafluoroethylene (PTFE) and bovine absorbable. For these observations made so critical defects (which have no spontaneous regenerative capacity) of the skull of rats by means of histomorphometric analysis and immunohistochemistry for osteopontin and tartrate-resistant acid phosphatase (TRAP). A total of 60 animals which were performed in critical bone defects, and treated with GTR procedures. The animals were divided into the following groups: control (no membrane), latex membrane, PTFE and bovine absorbable evaluated on days 7, 14 and 28 days. At 7 and 28 days the PTFE membrane showed greater bone formation (19.5 ± 3.69 and 50.5 ± 3.69, respectively, p <0.05) compared to the control group (9.5 ± 1, 91 and 22.75 ± 6.6, respectively) and the latex membrane (6.5 ± 3.78 and 32.5 ± 9.53, respectively) and bovine (11 ± 4.39 and 37.5 ± 3.5, respectively). At 7 days, the smallest bone tissue formation was noted in the group of the latex membrane (6.5 ± 3.78, p <0.05), compared to control (9.5 ± 1.91), membrane bovine (11 ± 4.39) and PTFE (19.5 ± 3.68). In 14 days, there was no difference between groups. The immunostaining showed no differences between groups and time analyzed (p> 0.05), but indicative of lower marking osteopontin in the group using the latex membrane, and TRAP in group PTFE membrane. Thus, we can say that the PTFE membrane showed the best results on the formation of bone tissue and bone markers indicate that the training activities and absorption against the use of different membranes in GTR technique in critical defects.